Study on failure mechanisms of composite box beams on wind turbine blades under extreme combined loading. Issue 15 (3rd June 2022) - Li, Jianwei; Wang, Jinghua; Yu, Liangfeng; Liu, Weisheng; Zhang, Lei'an
Abstract: A box beam is the main load-bearing component in the shell of a wind turbine blade. A set of loading equipment is utilized to perform a loading test under combined forces, to study the ultimate load and the strain response of the material. Based on the force-displacement response and the strain response of the material, the stressed state of the beam and web are summarized, and the damage of each component is described in detail. The debonding of the bonded joint and fracturing of laminate can be observed in the test results. The obvious buckling results in the initial breakage of bonded joints and a series of reactions cause the laminate to fracture, eventually leading to the structural failure of the box beam. In this test, the effect of a load applied in an edge-wise direction on the box beam is obvious, which is the key reason for the buckling.